Extraordinary items, income smoothing and market value of equity - Kamarudin, Khairul Anuar; Ibrahim, Muhd Kamil; Wan Ismail, Wan Adibah (Biro Penyelidikan & Perundingan, 2002)
This research examines issues related to the reporting of extraordinary items. The first issue concerns the changes of accounting standards on extraordinary items, which has limited the scope of extraordinary item. It is found that there are significant changes on the incidence of reported extraordinary items during the period after the adoption of the new standard. The findings supported the arguments that the new standard on extraordinary items had consequently abolished the items from financial statements. We also hypothesize that extraordinary items classification choice is a means used by companies to smooth income. Two types of statistical tests performed have confirmed the proposition that the disclosure of extraordinary items is subject to this type of manipulation during the period before the adoption of the new standard. Although it is proved that the broad definition of extraordinary items allows companies to manipulate income, evidence gathered from univariate regressions demonstrate that extraordinary items are significant for investors in valuing a firm's equity. Thus, investors took into accounts the extraordinary items even though it is disclosed 'below the line'.